2022
DOI: 10.1136/annrheumdis-2022-222341
|View full text |Cite
|
Sign up to set email alerts
|

2022 EULAR points to consider for remote care in rheumatic and musculoskeletal diseases

Abstract: BackgroundRemote care and telehealth have the potential to expand healthcare access, and the COVID-19 pandemic has called for alternative solutions to conventional face-to-face follow-up and monitoring. However, guidance is needed on the integration of telehealth into clinical care of people with rheumatic and musculoskeletal diseases (RMD).ObjectiveTo develop EULAR points to consider (PtC) for the development, prioritisation and implementation of telehealth for people with RMD.MethodsA multidisciplinary EULAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 58 publications
1
63
0
2
Order By: Relevance
“…In line with EULAR’s research agenda for patient self-management 30 and remote care, 31 we aimed to evaluate the accuracy, feasibility, usability and acceptability of two UA self-sampling devices (Tasso+ and TAP II) in patients with IMRD for measurement of autoantibodies and CRP levels.…”
Section: Introductionmentioning
confidence: 99%
“…In line with EULAR’s research agenda for patient self-management 30 and remote care, 31 we aimed to evaluate the accuracy, feasibility, usability and acceptability of two UA self-sampling devices (Tasso+ and TAP II) in patients with IMRD for measurement of autoantibodies and CRP levels.…”
Section: Introductionmentioning
confidence: 99%
“…No substantial differences between those followed by telemedicine only (n=121) and those who performed at least one in-person visit (n=76) were observed when multiple PROs (general health [GH], visual analogue scale [VAS] pain, functional assessment of chronic illness therapy [FACIT], rheumatoid arthritis disease activity index [RA-DAI], recent onset arthritis disability [ROAD], and PRO-CLinical ARthritis Activity [PROCLARA]) were considered. While awaiting for evidence to accumulate, a list of points to consider on remote care has been recently published by the EULAR to guide the implementation of telehealth for people with rheumatic diseases (49). Tailored care combining remote and face-toface attendance on the basis of shared decision-making and patient preference was stated as the first overarching principle.…”
Section: Innovations Towards the Near Future Emerging Evidence On Tel...mentioning
confidence: 99%
“…• Small observational studies consistently showed that telemedicine interventions were not associated with worse PROs compared to usual care or harm to patients, but interventions were heterogeneous as well as the measured outcomes. A guidance on remote care in rheumatic diseases has been published by the EU-LAR and telemedicine may assist pre-diagnostic processes, monitoring, and some non-pharmacological interventions (49). • ML applications in the field of rheumatology are growing and it is important to gain confidence with this powerful new analytics tool.…”
Section: Take Home Messagesmentioning
confidence: 99%
“…In contrast to emergency medicine (5), no objective, rheumatology triage criteria exists and this lack of standardized triage decisions hampers quality of care. The European Alliance of Associations for Rheumatology (EULAR) recently emphasized the added value of patient preassessment by telehealth to improve the referral process to rheumatology and help prioritization of people with suspected IRD (6).…”
Section: Introductionmentioning
confidence: 99%